79 Clinical health markers in dogs fed raw meat based or commercial extruded kibble diets. (30th November 2020) - Hiney, Kris M; Sypniewski, Lara; Pezeshki, Adel; McFarlane, Dianne
Abstract: Anecdotal reports of health benefits of raw meat-based diets (RMBD) for dogs include cleaner teeth, improved integument, and general health. However, little to no evidence is present in the scientific literature to support assertions of improved clinical outcomes in RMBD-fed dogs. We hypothesized that healthy dogs fed diets which have undergone less processing will show a clinical benefit and improved general health markers compared to dogs fed a highly processed diet. Enrollment criteria included healthy, client-owned adult dogs fed either RMBD or extruded kibble (EK) for > 1 year (RMBD n = 28; EK n = 27). Management history, clinical examination, hematology, urinalysis and serum biochemistry measures were collected for each dog. Dental, ear and coat scores were assigned by a blinded veterinary observer and a clinical composite score (CCS) calculated. Dogs fed RMBD showed an improved CCS and coat score compared to EK dogs (CCS: Mann Whitney test, P = 0.03; Coat: Fisher Exact Test, P = 0.04). Differences in blood analytes between feeding group were observed (Table 1). For each significant difference found by univariate analysis, forward stepwise linear regression was performed with age, breed, gender, and body condition score as independent factors. Serum alkaline phosphatase activity was 50% lower in dogs fed RMBD than those fed EK (P = 0.001). BUN was higher (P < 0.01) in RMBD dogs, while glucose concentration (P < 0.05) was lower in RMBD dogs compared to EK dogs. Platelet count was greater in RMBD dogs relative to EK group (P < 0.001). Owner management differed, with greater likelihood of management interventions and sporting activities in the RMBD group. RMBD may have mild clinical benefits and significant effects on blood analytes compared to EK, even when management was considered. Further work is needed to determine the impact of owner practices, diet processing, and nutrient content on health outcomes.